Tinjauan Kriminologis Terhadap Modus Baru Peredaran Psikotropika dan Obat-Obat Tertentu Melalui Toko Kosmetik - Primananda, Adhika; Giritikawati, Novi; Bayu Rastika, Dewa Gede (Eruditio : Indonesia Journal of Food and Drug Safety, 2023)
A new modus operandi (M.O.) has been identified in the illegal distribution of psychotropics and certain frequently abused drugs (OOT), that is, by using cosmetic shops as a distribution facility. This study aims to describe this phenomenon and provide intervention recommendations. The study was conducted using a qualitative method, which involved collecting secondary data through administrative data and news tracking. The data was then verified through interviews with relevant parties and field observations. The data collected showed increasing cases in at least three provinces: DKI Jakarta, Banten, and West Java. The M.O. is characterized by the high traffic of male teenagers who transact quickly at cosmetic shops with motorcycles on standby. The shops usually sell a small number of cosmetics that are dusty or expired and compacted on the storefront to cover drugs. An exciting finding was that a specific regional community played a role in the development of this M.O. However, the authorities' actions have not been effective, as several shops that have been prosecuted have committed violations again. If examined from a criminological perspective, one of the reasons why perpetrators choose to sell drugs illegally is due to the perpetrator's adaptation to anomie conditions, where expectations of success and wealth are difficult to achieve by conventional means. In pursuing these expectations, perpetrators make rational decisions to maximize profits and minimize costs/risks. Regional community groups are also formed because of rational choices and become a cultural model of organized crime groups.